Retrospective analysis of diagnosis and treatment in 9 cases of childhood-onset methylmalonic acidemia in China - Fan, Chao; Xu, Li; Gan, Siyi; Wu, Liwen; Yang, Haiyan; Ning, Zeshu (Frontiers in Neurology, 2025)
BackgroundMethylmalonic acidemia (MMA) lacks specific clinical manifestations, often leading to misdiagnosis and underdiagnosis by clinicians.MethodsWe retrospectively analyzed the clinical data of children with MMA admitted to the Department of Neurology, Hunan Children’s Hospital, from April 2015 to February 2024.ResultsA total of 9 children with MMA were included. The age at onset ranged from 1 month and 9 days to 8 years, with the time from onset to diagnosis extending up to 1 year and 2 months. Among them, 7 cases were early-onset and 2 were late-onset. Eight cases presented with neurological symptoms, including recurrent seizures, global developmental delay, mental and behavioral abnormalities, and disturbances of consciousness. One case was asymptomatic and confirmed via neonatal screening. Blood biochemistry showed elevated levels of lactic acid, homocysteine, ammonia, alanine aminotransferase, and glucose. All 9 patients received treatments such as vitamin B12 and L-carnitine to improve energy metabolism. Among them, seven achieved favorable clinical outcomes, while two had poor outcomes: one patient with MMACHA compound heterozygous variants (c.609G > A/p. Trp203* and c.658-660del/p. Lys220del*) died due to treatment failure, and the other experienced a poor outcome from delayed intervention.ConclusionEarly-onset MMA is more common, and its clinical manifestations are non-specific. Clinicians should be vigilant about genetic metabolic etiologies in patients with early-onset MMA characterized by recurrent seizures and developmental delay, late-onset MMA with mental and behavioral abnormalities or consciousness disturbances, and those with abnormal metabolic indicators. It is recommended to actively perform blood and urine tandem mass spectrometry and genetic analysis to confirm the diagnosis. The MMACHA c.658-660del (p. Lys220del*) variant may be associated with a poor prognosis in MMA patients.